THE AESTHETICS OF FRONTING AND DELAYING THE POEM "THE PROCESSIONS" BY (GIBRAN KHALIL GIBRAN) AS A MODEL (World Bulletin of Social Sciences, 2022)
Fronting and delaying is one of the rhetorical techniques that enriches the poetics of the text and gives the author more space to express the emotional states that are intrinsic to him. Fronting and delaying also stimulates the recipient's linguistic and rhetorical capabilities to discover the reasons and motives that disrupt the simple linguistic system, and the study sought to determine these reasons in Gibran's poetry. Khalil Gibran was influenced by the expressive forces concealed in the movements of words and their placement along the poetry line. This study examined the utterances of the imams of Arabic rhetorics in light of their soundness in analyzing Gibran's approaches. Khalil Gibran, and the study endeavored to interpret the aesthetics of fronting and delaying in various literary situations
Keywords: Presentation; delay; rhetoric; application